Examining the sociocultural sensitivity of subjective drunkenness: Comparing Arab and Jewish Israeli pub patrons. (20th March 2017) - Sznitman, Sharon R.; Bord, Shiran; Elias, Wafa; Gesser‐Edelsburg, Anat; Shiftan, Yoram; Baron‐Epel, Orna
Abstract: Introduction and Aims: Subjective drunkenness measures may be useful screening tools for alcohol‐related problems. However, if self‐reported drunkenness is influenced by social and cultural understandings, the measure may not predict drinking patterns equally across different sociocultural groups. The current study aims to determine whether the two main sociocultural groups in Israel (Arabs and Jews) are equally likely to report drunkenness at comparable levels of breath alcohol content (BrAC). Design and Methods: A cross‐sectional study was conducted among 901 Jewish and 225 Arab Israeli pub patrons. Respondents were interviewed as they exited pubs between midnight and 4 am. In addition to sociodemographic data, respondents reported whether they felt drunk at the time of the interview, after which they provided breath samples to determine BrAC. A logistic regression model tested whether there were differences in the probability of reporting drunkenness between Arabs and Jews holding BrAC levels and other background variables constant. Results: Arabs had higher BrAC levels than Jews (M = 0.19 vs. M = 0.13, P ≤ 0.0001) but a lower proportion of Arabs reported drunkenness than Jews (22% vs. 43%). Adjusted logistic regression showed that at all levels of BrAC, Jews had a higher probability of reporting drunkenness than Arabs (odds ratio = 6.40, P ≤ 0.0001). Discussion and Conclusions: Subjective drunkenness is likely to be influenced by cultural factors and may thus not reflect objective drinking patterns equally across different groups within the same society. This is likely to limit its usefulness as a screening tool for alcohol abuse and problems. [Sznitman SR, Bord S, Elias W, Gesser‐Edelsburg A, Shiftan Y, Baron‐Epel O. Examining the sociocultural sensitivity of subjective drunkenness: Comparing Arab and Jewish Israeli pub patrons.